Coronavirus pandemic and low oil prices putting pressure on the Gulf countries - Dawud Ansari; Hella Engerer (DIW Weekly Report, 2020)
The coronavirus pandemic has affected the Gulf countries in a particular way. In addition to the direct consequences of the pandemic, the spread of the coronavirus has led to a collapse in demand for the Gulf countries' most important source of revenue: oil. Its price, which had fallen initially due to the price war between Saudi Arabia and Russia, collapsed in spring 2020. Although it recovered somewhat afterwards, no rebound is in sight. Market simulations by DIW Berlin that analyze the future price development demonstrate there is a clear risk of the downward trend continuing in the short term. As a result, export revenue is likely to further decline in the Gulf states. The countries' fiscal space will shrink due to pandemic-related additional expenses as well. Generally, long-term challenges faced by this region, such as diversification and the possibility of a global energy transition, are at the risk of not being properly addressed.
Keywords: Q31; Q40; C69; N15; N55; O53; 330; oil price; GCC; Covid-19; diversification; Saudi Arabia